2019
DOI: 10.1007/s10596-019-09904-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of regularized ensemble Kalman filter and tempered ensemble transform particle filter for an elliptic inverse problem with uncertain boundary conditions

Abstract: In this paper, we focus on parameter estimation for an elliptic inverse problem. We consider a 2D steady-state singlephase Darcy flow model, where permeability and boundary conditions are uncertain. Permeability is parameterized by the Karhunen-Loeve expansion and thus assumed to be Gaussian distributed. We employ two ensemble-based data assimilation methods: ensemble Kalman filter and ensemble transform particle filter. The formal one approximates mean and variance of a Gaussian probability function by means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…According to the theory in [27], α n must be carefully selected, together with the stopping criteria, in order to ensure the stability of the LM scheme. The approach for selecting α n in the LM proposed in [27] has been adapted to the EKI framework in [2,16], and subsequently used in [3,12,14,[28][29][30]. As we discuss in the next section, this approach relies on tuning parameters that, unless carefully chosen, can lead to unnecessary large number of iterations n * .…”
Section: The Inverse Problem Framework With Ensemble Kalman Inversionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the theory in [27], α n must be carefully selected, together with the stopping criteria, in order to ensure the stability of the LM scheme. The approach for selecting α n in the LM proposed in [27] has been adapted to the EKI framework in [2,16], and subsequently used in [3,12,14,[28][29][30]. As we discuss in the next section, this approach relies on tuning parameters that, unless carefully chosen, can lead to unnecessary large number of iterations n * .…”
Section: The Inverse Problem Framework With Ensemble Kalman Inversionmentioning
confidence: 99%
“…The numerical results of [2] showed that EKI-LM enabled stability and accuracy for sufficiently large ensembles. Further work that has explored EKI-LM can be found in [3,28,29] as well as some practical applications including seismic tomography [14], modelling of intracraneal pressure [12] and time fractional diffusion inverse problems [30].…”
Section: Eki As An Iterative Solver For Identification Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the framework of nonlinear Kalman filters, to overcome several limitations of the linear Kalman filter, the values of the initial or boundary conditions can be incorporated into the particles or members. Dubinkina and Ruchi (2020), 33 ) Wen et al (2020), 34 ) and Nakamura et al (2021) 35 ) have dealt with inverse analyses using nonlinear Kalman filters for which both the material parameters and boundary conditions are uncertain. Hence, the third category of the above classification corresponds to the prototype of the present DA technique.…”
Section: Kalman Filters and Bayesian Methodsmentioning
confidence: 99%
“…Within the framework of nonlinear Kalman filters, to overcome several limitations of the linear Kalman filter, the values of the initial or boundary conditions can be incorporated into the particles or members. Dubinkina and Ruchi (2020), 33) Wen et al…”
Section: ½9mentioning
confidence: 99%